Multiple cerebral infarcts: a rare complication of neurosarcoidosis. Issue 3 (30th January 2019) - Harris, Matthew John; Cossburn, Mark Daniel; Pengas, George
Abstract : A 52-year-old man experienced a relapse of neurosarcoidosis, characterised by obstructive hydrocephalus and multiple posterior circulation infarcts. He was taking methotrexate, but his prednisolone was being weaned because of adverse effects. Stroke is rare in neurosarcoidosis and typically relates to granulomatous inflammation with a predilection for the perforator arteries. Sarcoidosis generally responds well to corticosteroids; however, patients with leptomeningeal involvement usually require additional immunosuppression as relapses can occur on weaning of corticosteroids. It is worth considering tumour necrosis factor-α antagonists for cases that progress despite first-line therapy.